Analisis Risiko Pembiayaan Mudharabah di Bank Syari’ah - Yusuf, Miranda Azizah; Febriyani, Elza; Anggraini, Mela; Lestari, Anjung Peby (JIOSE: Journal of Indonesian Sharia Economics, 2023)
Risks and obstacles to the implementation of mudharabah financing are one of the factors behind the low development of mudharabah financing in Islamic banks compared to other financing products. To anticipate risks and to enhance the development of mudharabah financing in Islamic banks, it is necessary to identify and in-depth study the risks of implementing mudharabah financing in Islamic banks so that strategies and solutions for these risks can be found. This research was conducted for this purpose by using quantitative research methods. The results of this study indicate that there are risks inherent in this financing, namely agency problems, adverse selection, moral hazard, and other risks that have not been studied in this study. These risks are a particular challenge for Islamic banks to implement mudharabah financing. The results of this study offer several strategies that can be carried out by Islamic banks in anticipating some of these risks, namely conducting analysis of prospective customers who are really good, conducting post-contract visits, providing managerial assistance as well as in preparing good and correct financial reports, conducting inspections and periodic monitoring, as well as immediately making decisions and following up when data is found that are not suitable for the implementation of the business carried out by the mudhorib. The solutions presented in this study can be further developed to support the implementation of mudharabah financing in Islamic banks.